1988
DOI: 10.2105/ajph.78.1.78
|View full text |Cite
|
Sign up to set email alerts
|

Marital status and the risk of suicide.

Abstract: No recent United States study has previously calculated national suicide rates by marital status for specific age, race, and sex categories in order to better identify high-risk groups for suicide. We used national vital statistics and census data to calculate marital-status-specific rates. Results show that for each marital status group, by age and sex, married persons have the lowest suicide rates and young widowed males have exceptionally high rates. (Am J Public Health 1988; 78:78-80.)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

13
104
1
9

Year Published

1991
1991
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 197 publications
(127 citation statements)
references
References 6 publications
13
104
1
9
Order By: Relevance
“…34 Marriage, however, is often reported as a protective factor against suicide. 35,36 Given these conflicting findings, further investigation is merited to clarify the role of marital status in suicide risk.…”
Section: Discussionmentioning
confidence: 99%
“…34 Marriage, however, is often reported as a protective factor against suicide. 35,36 Given these conflicting findings, further investigation is merited to clarify the role of marital status in suicide risk.…”
Section: Discussionmentioning
confidence: 99%
“…Depression, 2,6 schizophrenia, [32][33][34] alcohol and illicit drug use, 35,36 suicidal ideation and suicide attempts, 11 developing cancer, 37-39 not being married, and otherwise being socially isolated 40,41 are risk factors for suicide that are more common among smokers than among nonsmokers. Compared with nonsmokers, smokers also tend to act out hostility and have obsessional traits and anxiety.…”
Section: Discussionmentioning
confidence: 99%
“…Among non-spinal injured persons, those who are married have been shown to have lower suicide rates than those who have never been married, those who are divorced, or those who are widowed (Smith et al, 1988). Since previous studies have shown that divorce rates are higher and marriage rates are lower among persons with SCI than comparable individuals from the general population (DeVivo et al, 1985;, future studies should consider the effect of marital status on the suicide rate in the SCI population.…”
Section: Discussionmentioning
confidence: 99%